B. F. SKINNER'S SCIENCE AND HUMAN BEHAVIOR: ITS ANTECEDENTS AND ITS CONSEQUENCES - Catania, A. Charles (Journal of the experimental analysis of behavior, 2003)
Skinner's Science and Human Behavior marked a transition from a treatment of behavior that took physics as its reference science to one that emphasized behavior as a fundamental part of the subject matter of biology. The book includes what may be Skinner's earliest statement about the similarity of operant selection to Darwinian natural selection in phylogeny. Other major topics discussed in the book included multiple causation, private events, the self, and social contingencies. Among the important antecedents were Skinner's own Behavior of Organisms and Keller & Schoenfeld's Principles of Psychology. Current developments in education, behavioral economics, and some behavior therapies can be attributed at least in part to Skinner's seminal work. The effective behavioral analysis of governmental and religious systems will probably depend on elaborations of our understanding of verbal behavior.